Hermetic storage for control of common bean weevil, Acanthoscelides obtectus (Say). (March 2016) - Freitas, R.S.; Faroni, L.R.A.; Sousa, A.H.
Abstract: This study evaluated hermetic storage as a method of controlling Acanthoscelides obtectus (Coleoptera: Chrysomelidae: Bruchinae) in stored beans. Recently harvested "vermelhinho" cultivar of the common red bean was used, which had already been infested by A. obtectus in the field. Beans with a moisture content of 15.0% wet basis were stored in silo bags (3 kg), plastic bottles (1.5 L), or non-hermetic glass containers (3 L) (control) for 120 days. The packages were stored in an acclimatized chamber at 25 °C with a relative humidity of 70 ± 5%. At time intervals of 0, 30, 60, 90, and 120 days, three packages of each treatment were opened, and analyses were performed to assess the infestation percentage by insect pests, moisture content, density, electrical conductivity, germination percentage, and cooking time. There was no increase in infestation by A. obtectus in the grains stored in the silo bags and plastic bottles during the 120 days of storage; however, there was a significant increase in infestation in the grains in non-hermetic storage (control). The quality of the beans correlated with infestation; it was not altered in the hermetic storage systems and decreased in the control sample. Hermetic storage of common beans is an effective tool in the control of A. obtectus . Highlights: Hermetic storage of common bean controlled infestation by Acanthoscelides obtectus (Say). Airtight storage in silo bags and plastic bottles inhibited the development of insects. The quality of beans stored hermetically was preserved.